An Analysis of Code-Mixing in The Novel "Tentang Kamu" by Tere Liye - Raflis Raflis; Mouren Mouren Dian Agustin (Jurnal Ilmiah Langue and Parole, 2023)
This thesis deal with the types of Code Mixing found in Tere Liye’s Novel ”Tentang Kamu”. The thesis is focused on analyzing the code mixing used in the text within the novel. The main purpose of this thesis is to find out the types of Code Mixing in Tere Liye’s Novel ”Tentang Kamu”, to find out the most used type of the Code Mixing and to analyze the reasons and functionality of the particular Code Mixing used. The data of this study is 167 clauses containing code mixing that found in in Tere Liye’s Novel ”Tentang Kamu”. This research was conducted by using Descriptive Qualitative Research. The technique used to collect the data was documentary technique reading, studying, and analyzing all the data. The data were analyzed by using Hoffman theory of Code Mixing. Based on the data analysis, it was found that there were three types of Code Switching found in Tere Liye’s Novel ”Tentang Kamu” which is Intra-sentential Code Mixing, Intra-sentential Code Mixing and Involving Change of Pronunciation Code Mixing. Furthermore, There are seven functions Code Mixing that is found within the text in Tere Liye’s Novel ”Tentang Kamu”, which is Talking About Particular Topic, Quoting Somebody Else, Being Emphatic about Something, Interjection, Repetition Used for Clarification, Intention of Clarifying the Speech Content for Interlocutor, and Expressing Group Identity. The most dominant types of Code Mixing used in Tere Liye’s Novel ”Tentang Kamu” was Intra-sentential Switching with 134 clauses out of 167 clauses found in the text (80,2%). Furthermore, the most dominant functions of Code Mixing that is found within the text in Tere Liye’s Novel ”Tentang Kamu”, which is Talking About Particular Topic (126 clauses out of 167 clauses, 75,4%).